Introduction to annotated logics : foundations for paracomplete and paraconsistent reasoning /: foundations for paracomplete and paraconsistent reasoning. (2015) - Abe, Jair Minoro; Akama, Seiki; Nakamatsu, Kazumi
No abstract available